2019
DOI: 10.3390/cells8050479
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Selenoprotein F by Heat Shock Factor 1 during Selenium Supplementation and Stress Response

Abstract: Changes of Selenoprotein F (SELENOF) protein levels have been reported during selenium supplementation, stressful, and pathological conditions. However, the mechanisms of how these external factors regulate SELENOF gene expression are largely unknown. In this study, HEK293T cells were chosen as an in vitro model. The 5′-flanking regions of SELENOF were analyzed for promoter features. Dual-Glo Luciferase assays were used to detect promoter activities. Putative binding sites of Heat Shock Factor 1 (HSF1) were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…The upregulated GPX mRNA expression and GSH-PX activity that we detected indicated that Sel expression of mammary regulated the activities of milk Se-containing enzyme. It has been reported that the Se levels play a regulatory role for Sels, and Sel expression in animal tissues and cells were induced by Selenium supplement [32][33][34]. Since in the present study, nano-Se supplement resulted in significantly upregulated Sel mRNA expression (GPX, TXNRD, SelW, T, K and F), it is suggested that Se status is an important regulator of selenoprotein activity and expression in the mammary gland of dairy cows.…”
Section: Discussionsupporting
confidence: 55%
“…The upregulated GPX mRNA expression and GSH-PX activity that we detected indicated that Sel expression of mammary regulated the activities of milk Se-containing enzyme. It has been reported that the Se levels play a regulatory role for Sels, and Sel expression in animal tissues and cells were induced by Selenium supplement [32][33][34]. Since in the present study, nano-Se supplement resulted in significantly upregulated Sel mRNA expression (GPX, TXNRD, SelW, T, K and F), it is suggested that Se status is an important regulator of selenoprotein activity and expression in the mammary gland of dairy cows.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, the minor SELENOF haplotype was less responsive to selenium with regard to SECIS-mediated UGA recoding efficiency [ 37 ]. One molecular mechanism of how stressful conditions or selenium availability regulate SELENOF gene expression implicates heat shock factor 1 [ 44 ]. SELENOF resides in the short arm of human chromosome 1 [ 34 ], a region frequently characterized by genetic alterations in cancers [ 36 ], predominantly deletions, indicating that loss of heterozygosity at the SELENOF locus may contribute to the reduction in SELENOF levels or the unmasking of deleterious recessive mutations.…”
Section: Selenof’s Discovery Structure Cellular Localization and Expr...mentioning
confidence: 99%
“…In addition to Gpxs 1, 3 and 4, our results also revealed a relatively lower expression of Selenof in response to a low-Se diet, whereas its expression was significantly higher in both Se-adequate and Se-supplemented groups. As a "thioredoxin-like" selenoprotein, SELENOF is believed to perform oxidoreductase roles and is differentially expressed under adaptive and acute cellular stress conditions and changes to the Se levels [101][102][103]. It has been shown that, as an ER-resident selenoprotein, SELENOF is implicated in unfolded protein response (UPR), protecting the accumulation of unfolded or misfolded proteins in ER and thereby mitigating ER stress in cells [101].…”
Section: Expression Of Gpx1 Gpx3 Gpx4 Selenof Bcl-2 and P21mentioning
confidence: 99%
“…In any case, these findings reasonably highlight that expression of Selenof is regulated in a tissue-specific manner and responds differentially to Se levels. Our understanding of the regulation of this selenoprotein, both at transcriptional and translational levels, in different stress-related and pathologic conditions [102,103] is insufficient and further focused studies will help understand its physiological function in detail.…”
Section: Expression Of Gpx1 Gpx3 Gpx4 Selenof Bcl-2 and P21mentioning
confidence: 99%